Memory and the Future - Gutman, Yifat. author. aut Link
XI, 217 p.
Keywords: For those who study memory, there is a nagging concern that memory studies are inherently backward-looking, and that memory itself hinders efforts to move forward. Unhinging memory from the past, this book brings together an interdisciplinary group of prominent scholars who bring the future into the study of memory.